Himpunan Kisah PARA WALI - Raihanah; Rabiatul Adawiyah Othman (Petaling Jaya, Selangor : Hijjaz Records Publishing, 2018)
Consists of 40 Muslim saints stories.
Contains verses from the Qur'an and quotes from the Hadith.
Bibliography: pages 189-190.
Keywords: Islamic stories, Malay; Muslim saints; Islamic legends